Understanding the travelers’ intention towards Virtual tourism adoption using value-based Adoption model - Kelvin Lim; Siti Nor Bayaah Ahmad; Nor Asiah Mahmod; Irma Wani Othman; Suddin Lada (2022)
Virtual Tourism (VT) is defined as a novel concept that enables potential tourists to enjoy tourist sites without visiting them physically. Nonetheless, VT remains a novelty for Malaysian tourists. Therefore, this study intends to ascertain travellers’ adoption intentions in Virtual Tourism via the use of a Value-based Adoption Model (VAM). Travellers in Malaysia aged 21 to 39 were the analytic unit in this study. A total of 302 usable responses were obtained from an online self-administered questionnaire and analysed using Partial Least Squares-SEM in conjunction with the SmartPLS programme. Prior to proceeding to the next questions, respondents were shown a film to gauge their level of acceptance of virtual tourism. The research findings indicate that perceived benefits are more influential to perceived value than perceived sacrifices. Results showed that the components of perceived benefits, namely perceived usefulness (β = 0.341, t = 6.552) and perceived enjoyment (β = 0.341, t = 6.552), had a considerable beneficial influence on perceived value. Perceived complexity is the only component of perceived sacrifices that has a substantial negative influence on perceived value (β = - 0.142, t = 2.758). In contrast, felt immersion (β = 0.059, t = 0.913), perceived expense (β = -0.020, t = 0.318), and perceived physical risk (β = -0.021, t = 0.350) were discovered to have no discernible impact on perceived value. Although the current study focused on a specific age group of clients, similar studies could be expanded in the future to include other groups with a variety of travel interests. The study’s results may aid tourism providers and marketers by indicating a direction in which they should concentrate their efforts and emphasise growing perceived benefits while minimising perceived sacrifices, because this would progressively but consistently boost profits.